Radiation necrosis presenting as pseudoprogression (PsP) during alectinib treatment of previously radiated brain metastases in ALK-positive NSCLC: Implications for disease assessment and management. Issue 3 (June 2015) - Ou, Sai-Hong Ignatius; Klempner, Samuel J.; Azada, Michele C.; Rausei-Mills, Veronica; Duma, Christopher
Abstract Objectives Radiation necrosis presenting as pseudoprogression (PsP) is relatively common after radiation and temozolomide (TMZ) treatment in glioblastoma multiforme (GBM), especially among patients with GBM that harbors intrinsic increased responsiveness to TMZ (methylated O6-methylguanine–DNA methyltransferase [MGMT] promoter). Alectinib is a second generation ALK inhibitor that has significant CNS activity against brain metastases in anaplastic lymphoma kinase (ALK)-rearranged (ALK+) non-small cell lung cancer (NSCLC) patients. Materials and methods We report 2 ALK+ NSCLC patients who met RECIST criteria for progressive disease by central radiologic review due to increased in size from increased contrast enhancement in previously stereotactically radiated brain metastases with ongoing extra-cranial response to alectinib. In both patients alectinib was started within 4 months of completing stereotactic radiosurgery (SRS). The enlarging lesions in both patients were resected and found to have undergone extensive necrosis with no residual tumor pathologically. PsP was incorrectly classified as progressive disease even by central independent imaging review. Conclusions Treatment-related necrosis of previously SRS-treated brain metastasis during alectinib treatment can present as PsP. It may be impossible to distinguish PsP from true disease progression without a pathologic examination from resected sample. High degree of clinical suspicion, close monitoring and more sensitive imaging modalities may be needed to distinguish PsP versus progression in radiated brain lesions during alectinib treatment especially if there is no progression extra-cranially.